2004
DOI: 10.1038/sj.ejcn.1601879
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical vitamin A deficiency in Israeli-Bedouin toddlers

Abstract: Objective: This study was designed to estimate the prevalence of and evaluate risk factors for subclinical vitamin A deficiency in Arab-Bedouin children at age 18 months, followed from birth. Design: Community-based, prospective, cohort study conducted in Rahat, a large Arab-Bedouin township, located near the city of Beer Sheva in the Negev region of southern Israel. Subjects: Healthy Bedouin infants (n¼117) from the township, born at Soroka University Medical Center (SUMC) in Beer Sheva, were randomly recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
3
12
0
2
Order By: Relevance
“…O IVA-CG também enfatiza a fortificação de alimentos, como um método de combate a DVA, assim como a educação nutricional, e estudos relativos ao aumento da biodisponinilidade da vitamina A em alimentos 69 . Mora et al, 1998Mora et al, 1998Villalpando et al, 2003Paez et al, 2002Castejon et al, 2004De Navarro et al, 1996Pedro et al, 2004Coles et al, 2004Feungpean et al, 2002Tan Z et al, 2002Khatib, 2002Singh & West Jr., 2004Schémann et al, 2002Asrat et al, 2002Oso et al, 2003Kassaye et al, 2001Gregory Jr et al, 1995Palafox et al, 2003 *RS -Retinol Sérico.…”
Section: Programas De Correção Da Dva Por óRgãos Governamentais No Mundounclassified
“…O IVA-CG também enfatiza a fortificação de alimentos, como um método de combate a DVA, assim como a educação nutricional, e estudos relativos ao aumento da biodisponinilidade da vitamina A em alimentos 69 . Mora et al, 1998Mora et al, 1998Villalpando et al, 2003Paez et al, 2002Castejon et al, 2004De Navarro et al, 1996Pedro et al, 2004Coles et al, 2004Feungpean et al, 2002Tan Z et al, 2002Khatib, 2002Singh & West Jr., 2004Schémann et al, 2002Asrat et al, 2002Oso et al, 2003Kassaye et al, 2001Gregory Jr et al, 1995Palafox et al, 2003 *RS -Retinol Sérico.…”
Section: Programas De Correção Da Dva Por óRgãos Governamentais No Mundounclassified
“…These two anthropometric parameters are indicators of acute and chronic malnutrition, which may be the cause of the identified VAD in these patients. Identification of the risk factors for low serum retinol will be helpful for all the community health programme developers and policymakers to develop new strategies for improving vitamin A status in at‐risk communities (21).…”
Section: Discussionmentioning
confidence: 99%
“…Findings of more recent surveys in China [81], India [82,83], Nepal [7], Nigeria [84], Brazil [85], Venezuela [86], Cambodia [87], and the Western Pacific [88] generally uphold the conservative estimates in Table 13.3. Some studies have identified vitamin A deficiency at levels of public health concern in populations not previously considered deficient, such as in Turkey [89,90] and among seminomadic Bedouin populations in Israel [91], where 15-20% of preschoolers have serum retinol concentrations below 0.70 µmol/L. Other studies have shown conditions to worsen amid conflict, such as in Afghanistan, where at least 7% of young children in Kabul City alone have xerophthalmia [92].…”
Section: Preschool-aged Childrenmentioning
confidence: 97%